Quantitative models in marketing research - Franses, Philip Hans, 1963- (Cambridge University Press, 2001)
"Recent advances in data collection and data storage techniques enable marketing researchers to study the characteristics of a large range of transactions and purchases, in particular the effects of household-specific characteristics and marketing-mix variables." "This book presents the most important and practically relevant quantitative models for marketing research. Each model is presented in detail with a self-contained discussion, which includes: a demonstration of the mechanics of the model, empirical analysis, real-world examples, and interpretation of results and findings. The reader of the book will learn how to apply the techniques, as well as understand the latest methodological developments in the academic literature." "Pathways are offered in the book for students and practitioners with differing statistical and mathematical skill levels, although a basic knowledge of elementary numerical techniques is assumed."--Jacket